A influência dos stakeholders no desempenho organizacional em empresas estatais federais - Moura, Rosicler Oliveira de (2016)
The purpose of this study is to know the influence of stakeholders on federal state-owned companies, associated with National Quality Foundation (Fundação Nacional da Qualidade - FNQ): who they are, how they are identified, how they have treated their own interests and translated into performance requirements, forms of interaction between the state corporations and its stakeholders and the influence of their needs in organizational decisions. Based on the literature about 'stakeholders and Model of Excellence in Management', recommended by FNQ, the available information has been sought in theoretical references and organizations, through exploratory and descriptive research, to expand the understanding and learning about the different groups that affect and are affected by the institutions. The stakeholders identified in the federal state-owned companies have been classified into the following eight categories: 1. Citizens (customers, consumers and users of infrastructure services); 2. Workforce (collaborator, employees, workers and labor force); 3. Government (public authorities, parliamentarians, control, regulatory and supervisory agencies); 4. Shareholders and investors 5. Partners; 6. Suppliers (internal and external) 7. Society (communities and civil society organizations); 8. Others (financial institutions, market analysts and others). This study contributed to the debate on the influence of stakeholders, concerning the importance of their impact on the organization's goals, involve different processes and interaction channels, demonstrated by some state companies, the search for alternatives that promote the satisfaction of the different entities with which it interacts, and concomitantly, it contribute to improve management and achievements of organizational objectives